A Full-Body Motion Capture Gait Dataset of Healthy Young Adults Walking Ramps Up and Down - Vielemeyer, Johanna; Tronicke, Lisa; Schreff, Lucas; Abel, Rainer; Lechler, Knut; Müller, Roy (Scientific Data, 2026)
3D motion capture data of healthy participants is of high value for research groups working in basic research, clinical settings, or the development of medical devices as a reference or for comparison purposes. This dataset provides kinematic and kinetic data from 13 healthy young adults (five women, eight men; mean age 28.2 ± 4.7 years) during ramp walking at three inclinations (0°, 7.5°, and 10°). Using a 3D motion capture system (Vicon Motion Systems Ltd) consisting of 10 infrared cameras, two video cameras and three force plates (Advanced Mechanical Technology, Inc.), data was recorded as participants walked up and down a 6 m instrumented ramp at self-selected speeds. In each trial, two consecutive strides over the force plates are captured. The dataset includes raw data and processes kinematic and kinetic data of the lower limb and upper body based on the Plug-in Gait full body model.
CRIS-Team Scopus Importer:2026-01-23